Strengthening Village Governance and Development of E-desita in Realizing Disability-Friendly Inclusive Villages in Ponorogo Regency - Lestari, Yuni; Eprilianto, Deby Febriyan; Megawati, Suci; Oktariyanda, Trenda Aktiva; Agustin, Cindy Pramita; Fitrianingrum, Aditya Pratiwi (Universitas Muhammadiyah Sidoarjo, 2023)
E-desita is a form of strengthening digital-based village archiving systems with the ultimate aim of strengthening village governance. Karangpatihan Village is one of the villages that has a high number of people with disabilities in Ponorogo Regency. Karangpatihan Village needs to strengthen village governance. The aim of this research is to collect data on the disabled community to support the realization of a disability-friendly inclusive village in Karangpatihan Village, Balong District, Ponorogo Regency. The method used in this research is the development method. The type of research that will be carried out uses the R&D (Research and Development) method starting from stages (1) research and information collecting, (2) planning, (3) developing a preliminary form of product, and (4) preliminary field testing. This research was conducted at the Karangpatihan Village Office, Balong District, Ponorogo Regency. This research produces an e-desita application that is used in managing population data, especially for people with disabilities in Karangpatihan Village